Large-scale hybrid energy systems for power networks containing renewable sources - Lim, Jenn An. (2013)
The aim of this report is to maximise the potential ways of harnessing the photovoltaic renewable sources incorporated with energy storage system and use as a method for Singapore. Modelling of photovoltaic cell, Vanadium Redox Flow Battery and energy management technique are implemented using Matlab Simulink. The approach of modelling is to use equations for all three models. The photovoltaic cell is implemented by considering the ideal state of the cells. The Vanadium Redox Battery is implemented using 39 cells and a power loss efficiency of 21% with a power rating of 3300W. The modelling of energy management techniques is implemented by using techniques like valley filling and peak shaving. The model results obtained show the characteristic of the photovoltaic cells and the behaviour of both Vanadium Redox Flow Battery and energy management technique while the charging and discharging process.